Brilliant Leadership Unlocking the Power of Innovation-Communication - Belasen, Alan (Taylor & Francis, 2024)
The need for restructuring and transforming business practices for the benefit of humanity and the environment is a major theme of this book. Interactivity and connectedness of people and things/data is transforming everything. Many organizations, even the traditional ones, have entered a process of transformation through innovation and rethinking their business models, which affects the way leaders communicate, lead, and co-create.Brilliant leadership is a new intellectual framework to guide strategists, gamechangers, senior executives, and aspiring leaders. This new framework is based on our current work on leadership development and focuses on what it means to become a brilliant leader. Brilliant leaders have an authentic personality, the willingness to engage people/teams, inspire others, facilitate (co-)innovation, and commit to making significant contributions (humanity, environment, ethics), and be relevant.